The Influence Of Disaster Preparedness Health Education Using Video Media On Students' Knowledge And Attitudes At SDN 1 Sukasari Tangerang City - Bangun Wijonarko; Dina Sri Mawaddah; Viyan Septiana (Universitas Malahayati Lampung, 2025)
ABSTRACT Indonesia is a country that has a high level of natural disaster vulnerability, such as volcanic eruptions, earthquakes, tsunamis, floods, landslides, and so on. Disaster education to reduce disaster risk in childhood is very important. Of this study was to determine the effect of education on student knowledge with video media in disaster preparedness at SD Sukasari. This research is a quantitative study (quasi experiment) with a pre test and post test approach with control group design. Determination of the sample using Non Probabiltiy sampling type by purposive sampling. Respondents of this study were third and fourth grade students of Sukasari Elementary School, which were calculated using paired categorical comparisons with 22 respondents in each group. The analysis used univariate analysis to see a description of the characteristics of respondents, bivariate analysis to determine differences in knowledge and attitudes about disaster preparedness education in both groups, paired data tested paired t-test or Wilcoxon non-parametric test if the data was not normally distributed. The results showed a p value of knowledge of 0.9, p value of attitude of 0.538 and p value of behavior of 0.878. This shows that there is no difference between video media and lectures. That both media have benefits in increasing the knowledge, behavior and attitudes of students at SDN Sukasari 1 Tangerang City. Keywords: Natural Disasters, education, video, knowledge, Behavior